Morphinic liver colic and its pathophysiology: 2a. part. Action of morphine on the Oddi sphincter and the common bile duodenal crossroads. Electromanometry in biliary surgery - Cosco Montaldo, Homero; Soto Carriquiry, Juan P (Cirugía del Uruguay, 2020)
Presented at session 23th October 1963